Metropolitan atmospheric microplastics: Characteristics and its inputs to fluvial system - Yichen Liu; Yujie Liu; Yuchuan Meng; Guodong Liu; Guangming Chai; Xiaohua Huang; Yu Chen (Journal of Environmental Sciences, 2026)

Experimental study on spray and combustion characteristics of biodiesel-kerosene blends at elevated temperature and pressure conditions - Shenghao Yu; Dong Xie; Jiao Wang; Yichen Xie; Chao Chen (Fuel, 2026)

Design of metastable peanut protein–polyphenol complex particles for tunable flow, interfacial, and gelation properties - Shishuai Cui; Shinuo Cao; Tianlong Xiao; Yichen Zheng; Fei Xiang; Lijuan Yu; Qiang Wang; Xiaojie Ma; Benu Adhikari; Aimin Shi (Food Chemistry, 2026)

Sublethal effects of field-recommended glyphosate exposure on the predatory insect Arma chinensis: Growth inhibition and reproductive costs - Zhihan Su; Wenyan Xu; Luyao Fu; Dianyu Liu; Xiaoyu Yan; Yu Chen; Yichen Wang; Chenxi Liu (Environmental Pollution, 2026)

Study on the improvement effect of water-based polyurethane/cellulose acetate composite on silty clay for slope ecological restoration in seasonally frozen soil regions - Xinhao Wu; Chenglong Yu; Libo Liu; Huanan Liu; Jiquan Zhang; Yichen Zhang; Qinze Du; Haoxin Chen (Ecological Engineering, 2026)

The AtRNC1-AtWTF1 protein complex is essential for chloroplast group Ⅱ intron splicing, ribosome biogenesis, and embryo development in Arabidopsis - Yichen Zhang; Xinyun Xu; Yajuan Li; Siwen Wei; Jiayi Shen; Qing-Bo Yu; Yong-Lan Cui (Plant Molecular Biology, 2026)

MoireStudio: A universal twisted electronic structure calculation package - Junxi Yu; Yichen Liu; Cheng-Cheng Liu (Computer Physics Communications, 2026)

Experimental study on mixed convective heat transfer over human body under low-speed turbulent wind - Siqi Zhou; Yichen Yu; Jianlei Niu; Kenny C.S. Kwok; Gang Hu (Building and Environment, 2026)

Developing an explicit heat and moisture transfer model for sweat-soaked clothing in human thermal comfort assessment using a sweating thermal manikin - Cheng Zhao; Yichen Yu; Jianlei Niu; Jintu Fan (Building and Environment, 2026)

Collaborative optimization pathway of provincial power generation structure in China - Yan Nie; Guoxing Zhang; Yutao Wang; Bin Su; Yichen Feng; Lean Yu (Mitigation and Adaptation Strategies for Global Change, 2026)

Prospective motion correction with data reacquisition based on fat navigators for T1-weighted brain MRI at 3T - Minqiang Jia; Bingbing Zhao; Tuo Yu; Jiayu Zhu; Xijing Zhang; Haohao Peng; Xin Ye; Yichen Zhou; Rongrong Xie; Xinju Zhang; Han Zhang; Xiaopeng Zong (Medical & Biological Engineering & Computing, 2026)

Structuring urban carbon metabolism through cross-sectoral and cross-media linkages: Evidence from a high-density city - Yu Lin; Jiahao Shi; Yichen Dong; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Sustainable Cities and Society, 2026)

Nutrient management modulates lignin accumulation in pomelo fruits: insights from metabolic pathways of guaiacyl lignin and p-hydroxyphenyl lignin - Changhong Lai; Yujia Xu; Yichen Hu; Pengfei Yu; Haomin Wang; Huafang Zeng; Jun Wang; Zhonghe Wang (Food Chemistry, 2026)

Recent Advances and Future Perspectives in the Integrated Management of Potato Bacterial Wilt - Shifeng Liu; Yichen Wang; Juqin Wang; Lang Yan; Xianjun Lai; Deshui Yu (Potato Research, 2026)

The flexible metabolism of Accumulibacter and prevalence of clade IIC due to nitrite stress in a denitrifying phosphorus removal sludge - Juan Ma; Haidong Jin; Wengqing Tian; Peng Wan; Yichen Zhang; Zhe Li; Yujun Guo; Xinyao Ma; Peng Wang; Xiaojun Yu (Process Safety and Environmental Protection, 2026)

High-titer de novo raspberry ketone production in Yarrowia lipolytica via precursor supply engineering and fed-batch fermentation optimization - Yuanyuan Li; Shuhao Niu; Zixuan Wang; Yichen Wang; Xiaojuan Zhang; Yu Deng; Shenghu Zhou (Bioresource Technology, 2026)

Cost-Effective new energy management strategies for hybrid energy storage solutions - Shuhan Wei; Yichen Sun; Chengzhi Yu; Shon Ming (Energy and Buildings, 2026)

Low-carbon renovation of old residential blocks: An envelope-focused assessment framework for carbon reduction effects and economic benefits - Shen Xu; Yichen Dong; Hongxin Guo; Zhen Yu; Bo Pan; Congyue Qi; Gaomei Li (Energy and Buildings, 2026)

Skin-triggered Janus physical cooling patches for prolonged evaporative cooling and superior comfort - Junyi Lu; Fuzhou Niu; Tonghuan Zhan; Heng Wang; Haojun Luo; Yichen Tang; He Wang; Xiaohua Yu; Weijie Zhang; Hao Chen; Bing Xu (Chemical Engineering Journal, 2026)

Catalytic pyrolysis of wood-plastic composites using nickel-modified red mud for enhanced hydrogen and aromatic production - Yichen Yan; Huichao Suo; Cheng Peng; Zhengyi Wu; Lan-Lan Lou; Shuangxi Liu; Kai Yu (Bioresource Technology, 2026)

Dynamic cross-sector and media assessment of urban phosphorus metabolism: underlying mechanisms, environmental implications, and driving forces - Yichen Dong; Yu Lin; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Environment, Development and Sustainability, 2026)

Ribavirin acts as a candidate insect growth regulator: Providing sustainable control potential for Rhopalosiphum padi - Li Xu; Jingkun Li; Fei Miao; Zhiwen Zhao; Yichen Fu; Hengxu Yan; Sen Huang; Hao Yu; Runqiang Liu; Dongzhi Li (Crop Protection, 2026)

Resilience assessment of interdependent transit networks: an indifference perception threshold-based approach - Yichen Liang; Yajuan Deng; Chen Zhang; Ketong Hao; Yujie Guo; Yu Li; Liangbin Cui (Transportation Research Part D: Transport and Environment, 2026)

DeSUMOylation of Spastin Enhances AMPA Receptor Recycling and Synaptic Plasticity via IST1-Dependent Endosomal Sorting - Jiong Li; Bingyu Ren; Yichen Yin; Kedong Chen; Meiying Chen; Guangyin Yu; Guoqing Guo; Jifeng Zhang; Caihui Cha; Laijian Wang (Molecular Neurobiology, 2026)

Model-based estimation of microplastic stock in China’s reservoirs: A continental assessment - Yu Chen; Yuchuan Meng; Guodong Liu; Xiaohua Huang; Ke Chen; Yichen Liu; Shijing Wan (Gondwana Research, 2025)

Seasonal disparities in vertical distributions of microplastics and driving factors in a deep reservoir - Yu Chen; Yuchuan Meng; Guodong Liu; Xiaohua Huang; Yichen Liu; Dongsheng Zhu; Bo Ren (Journal of Hazardous Materials, 2025)

Unraveling hiatuses in black shales: Mechanisms and implications from the Lower Silurian Longmaxi Formation, South China - Yichen Liu; Benzhong Xian; Qianran Wu; Zhiyong Lu; Haocheng Shi; Mingjin Wu; Zhiyun Yu; Lin Zhao; Junyang Geng; Haiying Chen (International Journal of Coal Geology, 2025)

Comparative analyses of thermal transport in cellulose at crystalline, paracrystalline and amorphous states - Yichen Hou; Ruo-Yu Dong (Carbohydrate Polymers, 2025)

Phosphorylation of a conserved TBXT threonine residue is vital to vertebral development - Shuxia Chen; Chennan Liu; Ying Zhao; Lingbo Wang; Rui Peng; Lei Lu; Qian Yu; Yichen Jin; Jinsong Li; Xueyan Yang; Yunping Lei; Hongyan Wang (Science China Life Sciences, 2025)

Latin Hypercube Sampling improves estimation of the GEDI-based forest canopy height: a case study in Jiangxi Province, China - Yanming Shu; Shaoyu Zhang; Yichen Luo; Jun Yu; Jin Chen; Shuhua Qi; Yong Ge (International Journal of Remote Sensing, 2025)

Differential response of runoff-sediment hysteresis relationships to watersheds hydrological structural connectivity - Taoxi Li; Ming Lei; Gang Sun; Qian Zeng; Yu Long; Yichun Ma; Yichen Yin; Peiyao Xiao; Jiale Ye; Zhongwu Li; Yaojun Liu (Journal of Hydrology, 2025)

Preparation high-efficiency NH2-MIL-125@g-C3N4 NADH photo-regeneration catalyst for enzymatic conversion of furfural to furfural alcohol - Shuaizhe Li; Xingyong Li; Senshen Yu; Qingtao Wang; Na Liu; Yichen Nie; Xuexiang Fu; Mengke Dong; Haolin Li; Yanliang Guo; Phidsavard Keomeesay; Shijie Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

High-frequency sequence patterns in lacustrine basins: Insights from delta-hyperpycnal flow systems in the Middle Jurassic shale interval, Sichuan Basin, China - Haocheng Shi; Benzhong Xian; Yichen Liu; Zhiyun Yu; Lin Zhao; Junyang Geng; Rongheng Tian; Qianran Wu; Li Liu; Yujie Shuai; Yi Shu (Sedimentary Geology, 2025)

Early-life indoor environmental exposures and COVID-19 outcomes in Chinese preschool children: A secondary analysis of a multicenter study - Chan Lu; Jing Ma; Zipeng Qiao; Yichen Yu; Wanxue Xu; Wewei Liu; Faming Wang (Journal of Hazardous Materials, 2025)

Salix×jiangsuensis ‘J172’ enhanced lead tolerance under flooding stress by regulating the rhizosphere bacterial assembly and functions - Yichen Xu; Yazhen Chen; Yini Cao; Jason C. White; Hao Yu; Chuanxin Ma; Wende Yan; Baoshan Xing (Environmental Pollution, 2025)

Genetic Correlations and Causalities between Alzheimer’s Disease and 35 Biomarkers in Blood and Urine - Sheng Zhang; Yu-Lin Yao; Yichen Li; Xiaofan Zhang; Yong Wu (Molecular Neurobiology, 2025)

Numerical and Experimental Investigation of a Ducky Wave Energy Converter and Its Impact on Floating Ocean Wind Turbines - Tao Tao; Yu Dong; Xinran Guo; Shi Liu; Yichen Jiang; Zhiming Yuan (Journal of Marine Science and Engineering, 2025)
The ocean represents a vast reservoir of energy. To address the issue of wave-induced motion in floating wind farms—particularly pitch motion—while harnessing the otherwise dissipated wave energy for power generation, this study proposes an integrated solution. Specifically, a duck-shaped wave energy converter incorporating mooring and power take-off systems is introduced. By combining computational fluid dynamics with experimental fluid dynamics methodologies, the performance of the device was systematically evaluated and its key parameters—including floating attitude, power take-off damping, and mooring configuration—were optimized. Furthermore, results indicate that deploying the duck-shaped converter around the periphery of a wind farm can reduce the wave-induced motion amplitude of the floating wind turbine platform by more than 70%, especially in terms of pitch motion, thereby significantly improving the operational efficiency and structural stability of the wind turbines.

Understanding spatial differences in CO2 emissions between passenger and freight transportation - Yuliang Zhang; Yifan Chen; Yichen Wang; Chengcheng Yu; Xiqun (Michael) Chen; Der-Horng Lee (Transportation Research Part D: Transport and Environment, 2025)

Enlarged Perivascular Spaces (EPVS) Associated with Functional and Cognitive Outcome After Aneurysm Subarachnoid Hemorrhage (aSAH) - Haichao Wang; Qiuyue Yu; Wenyi Zhang; Shengqi Yao; Yun Zhang; Qiong Dong; Yichen Zhao; Jinxing Lin; Xueyuan Liu; Li Gong (Translational Stroke Research, 2025)

Quinoa greens as a novel plant food: a review of its nutritional composition, functional activities, and food applications - Huange Huang; Qiang Wang; Jianxin Tan; Chunxiang Zeng; Junying Wang; Jingwei Huang; Yichen Hu; Qi Wu; Xiaoyong Wu; Changying Liu; Xueling Ye; Yu Fan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Editorial: One climate, one urban, one health - Guangtao Fan; Yichen Yu; Meng Gao; Ayyoob Sharifi; Minal Pathak; Kai Zhang; Pablo Fernández de Arróyabe Hernáez; Qihong Deng (Sustainable Cities and Society, 2025)

Exploring heterogeneity in evacuation decision of urban residents between utility and regret decision rules under a flood hazard - Zeqian Jin; Yichen Wang; Chen Li; Chengcheng Yu; Xin Ye; Jiantao Mu (Sustainable Cities and Society, 2025)

Convective heat transfer coefficients over human body under non-uniform approaching airflow conditions - Xinzi Xu; Yichen Yu; Hao Hong; Gang Hu; Jianlei Niu (Energy and Buildings, 2025)

Melatonin integrates multiple biological and phytohormonal pathways to enhance drought tolerance in rice - Chanjuan Mao; Luyao Wang; Yichen Mao; Yingyin Li; Yizhi Peng; Yixuan Fan; Jiyuan Li; Yu Zhu; Xiaofeng Xu; Peng Li (Planta, 2025)

Design and Performance Study of a Six-Bar Mechanism Underwater Robot Based on Cownose Ray Bionics - Yichen Chu; Xiaohan Wang; Tiancheng Hao; Yanhui Fu; Yubing Duan; Tianbiao Yu (Journal of Marine Science and Engineering, 2025)
This paper focuses on the formidable challenges that underwater robots encounter in complex marine environments. To address these issues, inspired by the cownose ray, an innovative scheme is proposed, utilizing four six-bar mechanisms to mimic its pectoral fin movement. Subsequently, the paper elaborates on the design, computation, and simulation of the bionic pectoral fin mechanism. A Watt-type six-bar mechanism is adopted, and by axially overlaying two scaled-identical mechanisms and setting a phase difference, the pectoral fin waving of the cownose rays is simulated. SolidWorks and ADAMS are employed for precise modeling and simulation. Following this, an experimental prototype is constructed, with the rod assembly produced by subtractive machining. Motion capture and six-dimensional force experiments are then conducted to evaluate its motion dynamics and propulsion efficacy. The experimental results demonstrate that when the two pectoral fins on either side flap synchronously or inversely, the robot can generate varying thrust, lift, and lateral forces, enabling smooth advancement and turning. These findings validate the feasibility and efficacy of bionic design, offering innovative concepts and methodologies for underwater robot development.

Tight origin and hydrocarbon potential of shell interlayers in shale: A case of Lower Jurassic Dongyuemiao member, Sichuan Basin, China - Zhiyun Yu; Benzhong Xian; Zhenkui Jin; Qianran Wu; Yi Shu; Haocheng Shi; Junyang Geng; Lin Zhao; Yichen Liu (Marine and Petroleum Geology, 2025)

Janus antistatic protective clothing for personal sweat management and electrostatic protection - Haojun Luo; Yichen Tang; Xianchang Wu; Yu Zhang; Shuqiang Min; Yijie Zhu; He Wang; Tonghuan Zhan; Zixuan Xu; Zhihao Chen; Xiaohua Yu; Heng Wang; et al. (Chemical Engineering Journal, 2025)

Statistical and theoretical analysis of iodine spiking phenomena during steam generator tube rupture - Changdong Lu; Yichen Chen; Zhijun Li; Pingting Jiang; Chao Yu; Pengtao Fu (Annals of Nuclear Energy, 2025)

Enhanced bio-reduction of Cr(VI) using Shewanella putrefaciens CN32 mediated by Fe(III) minerals and riboflavin synergistically - Tianle Zhang; Haibo Li; Yichen Wu; Yajue Yuan; Yu Du (Biodegradation, 2025)

Reconstruction of 2‐m Air Temperature From ERA5 Reanalysis at Dome A, Antarctica - Yifan Wu; Yu Jiang; Yi Zhang; Yichen Li; Xin Chen; Wenqian Zhang; Xi Zhao (International Journal of Climatology, 2025)
In this study, we jointly used in situ air temperature from AWS and reanalysis data from ERA5 to make the first‐ever reconstruction of a 42‐year (1978–2020) air temperature time series for Dome A, Antarctica. By analysing the impact of environmental variables, we found that the 10‐m u‐component of wind was the predominant one for air temperature bias between ERA5 and AWS, followed by total cloud cover. Air temperature deviations between ERA5 and AWS during the period of 2005–2020 were successfully reduced by applying a random forest (RF) model, decreasing the bias by 0.52°C, the RMSE by 3.16°C and the MAE by 2.77°C. We next applied the RF model to predict the 2‐m air temperature difference which was added back to correct ERA5 from 1978 to 2004. This yielded an accurate time series of air temperature from 1978 to 2020. Using the innovative trend analysis method to analyse the temperature trend of the corrected data, we found that Dome A has experienced a gradual warming of 0.10°C dec −1 over the 42‐year period. Among the seasonal temperature changes, spring showed a significant warming trend of 0.57°C dec −1 , autumn and winter showed no significant warming, while summer showed a slightly cooling trend. Also, over the 42‐year analysis period, a stable oscillation period of ~28 year was observed. This cycle emerged as the dominant pattern, influencing the overall temperature evolution. The method proposed in this research, which combines machine learning with AWS to correct ERA5 air temperature data, holds the potential to address spurious changes of reanalysis data in long‐time series studies, thus improving the reliability of trend analyses.

Genetic analyses reveal wildfire particulates as environmental pollutants rather than nutrient sources for corals - Ke Liu; Bo Qin; Ruoxing Hao; Xiaoyan Chen; Yu Zhou; Wenqian Zhang; Yichen Fu; Kefu Yu (Journal of Hazardous Materials, 2025)

Exploring tourists' perceptions of ecosystem services in national parks to guide the optimization of management - Xiaomin Xiao; Yichen Yan; Yuxin Qi; Qiaoru Ye; Qiwen Yu; Keren He; Ruiming Xiao; Xue-Chao Wang; Xiaobin Dong (Journal of Cleaner Production, 2025)

Human body convective heat transfer coefficient under non-stationary turbulent wind - Siqi Zhou; Yichen Yu; Jianlei Niu; Kenny C.S. Kwok; Kapil Chauhan; Kam Tim Tse; Xinzi Xu; Sam Ho Yan Wong (Building and Environment, 2025)

Evaluating climate change impacts on building level steady-state and dynamic outdoor thermal comfort - Jiwei Zou; Yichen Yu; Mohammad Mortezazadeh; Henry Lu; Abhishek Gaur; Liangzhu Wang (Building and Environment, 2025)

Identification of Key Genes and Immune Characteristics of SASP in Acute Ischemic Stroke - Hanlu Cai; Huixue Zhang; Guanghao Xin; Shanshan Peng; Fanfan Xu; Nan Zhang; Yichen Li; Wei Zhang; Ying Li; Yingjie Ren; Yu Wang; Zhaojun Liu; et al. (Journal of Molecular Neuroscience, 2025)

Pedigree reconstruction based on target sequencing in Pacific white shrimp Litopenaeus vannamei - Junqing Yang; Yang Yu; Yizhou Zhou; Zhenning Bao; Yichen Liu; Jinsheng Sun; Fuhua Li (Aquaculture, 2025)

Influence of meteorological conditions on atmospheric microplastic transport and deposition - Yichen Liu; Zhongquan Nie; Yuchuan Meng; Guodong Liu; Yu Chen; Guangming Chai (Environmental Research, 2025)

Exploring the effect of clothing moisture content on heat and moisture transfer from the human body using a sweating thermal manikin - Cheng Zhao; Yichen Yu; Jianlei Niu; Yiying Zhou; Jintu Fan (Building and Environment, 2025)

Land certification, tenure security and off-farm employment: Evidence from China - Chuanhao Tian; Yichen Luo; Yu Teng (Land Use Policy, 2024)

Response of Ceratophyllum demersum L. and its epiphytic biofilms to 6PPD and 6PPD-Q exposure: Based on metabolomics and microbial community analysis - Xiang Li; Weitao Liu; Yichen Ge; Ruiying Shi; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Qi Wang; Jianling Wang; Fan Mo; Aurang Zeb; Miao Yu (Journal of Hazardous Materials, 2024)

Effects of dynamic airflows on convective cooling of human bodies − Advances in thermal comfort assessment and engineering design - Jianong Li; Siqi Zhou; Yichen Yu; Jianlei Niu (Energy and Buildings, 2024)

Efficient separation of per- and polyfluoroalkyl substances (PFAS) from water by aminated polyacrylamide hydrogel foam - Yichen Xu; Xueru Yu; Xinhao Wang; Yiqian Song; Wenran Wang; Ming Zhang; Deyang Kong; Zhanghao Chen; Cheng Gu (Chemical Engineering Journal, 2024)

The breaching mechanism of moraine dams with buried ice: A Review - Yunying Mou; Huayong Chen; Tao Wang; Hechun Ruan; Xiao Li; Yunhan Yu; Yichen Zhou; Haoyang Meng (Cold Regions Science and Technology, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

Environmental concentrations of 6PPD and 6PPD-Q cause oxidative damage and alter metabolism in Eichhornia crassipes - Yichen Ge; Jinzheng Liu; Ruiying Shi; Xiang Li; Aurang Zeb; Qi Wang; Jianling Wang; Yuexing Zhao; Miao Yu; Chuan Yin; Hongxia Xiong; Weitao Liu (Science of The Total Environment, 2024)

Comparative toxic effect of tire wear particle-derived compounds 6PPD and 6PPD-quinone to Chlorella vulgaris - Jinzheng Liu; Miao Yu; Ruiying Shi; Yichen Ge; Jiantao Li; Aurang Zeb; Zhipeng Cheng; Weitao Liu (Science of The Total Environment, 2024)

Onsite measurements of pedestrian-level wind and preliminary assessment of effects of turbulence characteristics on human body convective heat transfer - Siqi Zhou; Yichen Yu; Kenny C.S. Kwok; Jianlei Niu (Energy and Buildings, 2024)

Evaluation of immunogenicity and protective efficacy of outer membrane vesicles from Salmonella Typhimurium and Salmonella Choleraesuis - Yichen Tian; Shan Huang; Guodong Zhou; Xia Fei; Yu-an Li; Quan Li; Shifeng Wang; Huoying Shi (Veterinary Microbiology, 2024)

Soil moisture regulates soil-microbe-enzyme stoichiometries during recovery succession in patchily degraded alpine meadows on the Qinghai-Tibet Plateau - Yu Chai; Xilai Li; Chengyi Li; Yunqiao Ma; Zihan Song; Pei Gao; Yichen Ba; Weidong Wei (Ecological Engineering, 2024)

Layer-by-layer fabrication of alginate/polyethyleneimine multilayer on magnetic interface with enhanced efficiency in immuno-capturing circulating tumor cells - Yang Xiao; Zhiyi Zhou; Yifan Zuo; Xueyuan Wu; Yuping Liu; Yichen Li; Yuetong Gao; Xiashu Zhang; Yu Wang; Lili Hu; Chenglin Li (Analytica Chimica Acta, 2024)

Towards multi-views cloud retrieval accounting for the 3-D structure collected by directional polarization camera - Haixiao Yu; Xiaobing Sun; Bihai Tu; Rufang Ti; Jinji Ma; Jin Hong; Cheng Chen; Xiao Liu; Honglian Huang; Zeling Wang; Safura Ahmad; Yi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Responses in reef-building corals to wildfire emissions: Heterotrophic plasticity and calcification - Bo Qin; Kefu Yu; Yichen Fu; Yu Zhou; Yanliu Wu; Wenqian Zhang; Xiaoyan Chen (Science of The Total Environment, 2024)

Extraction of the spatial structure of Chinese fir plantations stands based on unmanned aerial vehicle and its effect on AGB - Xiang Huang; Yichen Chen; Hongru Tan; Yao Zhang; Shuhan Yu; Xiangyu Chen; Kunyong Yu; Jian Liu (Forest Ecology and Management, 2024)

GhHB14_D10 and GhREV_D5, two HD-ZIP III transcription factors, play a regulatory role in cotton fiber secondary cell wall biosynthesis - Shuaijie Li; Mengli Yu; Ghulam Qanmber; Mengru Feng; Ghulam Hussain; Yichen Wang; Zuoren Yang; Jie Zhang (Plant Cell Reports, 2024)

The effects of atmospheric nitrogen deposition in coral-algal phase shifts on remote coral reefs - Yichen Fu; Xiaoyan Chen; Yuchen Liu; Yuxiao Li; Kefu Yu (Frontiers in Marine Science, 2024)
Remote seawater has been considered a potential refuge for corals in the face of anthropogenic disturbances. However, these remote areas may receive increased atmospheric N deposition, and the ecological consequences remain unclear. This field survey revealed coral-algal phase shifts in the mid-north of the South China Sea. These shifts were observed in 44%, 13.6%, and 26.5% of the sampled reef sites at depths of 1-4 m, 5-8 m, and 10-15 m, respectively. Over 50% of sections in the deeper depths hosted fewer corals compared to shallower areas, coinciding with a higher abundance of macroalgae in the deeper layers. Furthermore, based on long-term observation of atmospheric N flux, laboratory experiments were conducted to explore the cause of coral declines. The results indicate that N supply efficiently promoted macroalgae growth. The saturation of N absorption by macroalgae occurred within 2 weeks, leading to nutrient accumulation in seawater, especially nitrate, which had a direct impact on corals. While moderate N fluxes appeared to mitigate coral bleaching, high N fluxes, even with a balanced P supply or medium level of nutrients with an imbalanced N/P ratio, can both increase the susceptibility of corals to heat bleaching. This study explains the coral-algal phase shift in remote and relatively deep seawater and improves understanding of the cause-and-effect relationship between atmospheric N deposition and coral reef decline.

Long-term spatiotemporal variations in surface NO2 for Beijing reconstructed from surface data and satellite retrievals - Zixiang Zhao; Yichen Lu; Yu Zhan; Yuan Cheng; Fumo Yang; Jeffrey R. Brook; Kebin He (Science of The Total Environment, 2023)

Study on initiation characteristics of oblique detonation induced by hydrogen jets in acetylene-air mixtures - Zhang Yichen; Xiang Gaoxiang; Gao Xiang; Yu Jia; Hu Xiquan; Xin Yirong; Li Danyang; Wang Qiu (Fuel, 2023)

Fluid tunnel research for challenges of urban climate - Yongling Zhao; Lup Wai Chew; Yifan Fan; Christof Gromke; Jian Hang; Yichen Yu; Alessio Ricci; Yan Zhang; Yunpeng Xue; Sofia Fellini; Parham A. Mirzaei; Naiping Gao; et al. (Urban Climate, 2023)

Camouflaging multifunctional nanoparticles with bacterial outer membrane for augmented chemodynamic/photothermal/starvation/chemo multimodal synergistic therapy of orthotopic glioblastoma - Yichen He; Yi Pan; Xin Zhao; Luyi Ye; Longcai Liu; Wenliang Wang; Meng Li; Dapeng Chen; Yu Cai; Xiaozhou Mou (Chemical Engineering Journal, 2023)

Insights into heavy metals shock on anammox systems: Cell structure-based mechanisms and new challenges - Yichen Wu; Yingxin Zhao; Yinuo Liu; Jiaojiao Niu; Tianyang Zhao; Xinhao Bai; Arif Hussain; Yu-You Li (Water Research, 2023)

A viscosity equivalent reduced-order method and its application to ship roll prediction - Yichen Jiang; Yu Dong; Peng Li; Hongyun Zong; Jiawen Li (Ocean Engineering, 2023)

Spatiotemporal variations in meteorological influences on ambient ozone in China: A machine learning approach - Tao Li; Yichen Lu; Xunfei Deng; Yu Zhan (Atmospheric Pollution Research, 2023)

Evaluating the effect of n-butanol additive on particulate matter emission in diesel engine - Qiren Zhu; Yichen Zong; Yong Ren Tan; Jieyao Lyu; Wenbin Yu; Wenming Yang; Markus Kraft (Fuel, 2023)

Genome-wide identification and expression analysis of wall-associated kinase (WAK) gene family in potato (Solanum tuberosum L.) - Huifang Yu; Weina Zhang; Yichen Kang; Yanling Fan; Xinyu Yang; Mingfu Shi; Ruyan Zhang; Yong Wang; Shuhao Qin (Plant Biotechnology Reports, 2022)

Strong partitioning of soil bacterial community composition and co-occurrence networks along a small-scale elevational gradient on Zijin Mountain - Xu Liu; Teng Yang; Yu Shi; Yichen Zhu; Mulin He; Yunke Zhao; Jonathan M. Adams; Haiyan Chu (Soil Ecology Letters, 2021)

Combining ability and genetic diversity under low-temperature conditions at germination stage of maize (Zea mays L.) - Jiayue Zhang; Yichen Li; Ziwen Zhang; Hong Di; Lin Zhang; Xuerui Wang; Zhenhua Wang; Yu Zhou (Euphytica, 2021)

Efficiency comparison of B6(Cg)-Tyrc−2j /J and C57BL/6NTac embryos as hosts for the generation of knockout mice - Yu’e Ma; Lei He; Lijie Xiang; Jie Zhang; Jing Wang; Wenjing Zhu; Wenni Cao; Yichen Zhu; Man Gao; Fei Zhou; Zhiwei Liu (Transgenic Research, 2021)
Careful selection of the host embryo is critical to the efficient production of knockout (KO) mice when injecting mouse embryonic stem (mES) cells into blastocysts. B6(Cg)-Tyr c−2j /J (B6 albino) and C57BL/6NTac (B6NTac) strains of mice are widely used to produce host blastocysts for such procedures. Here, we tested these two strains to identify an appropriate match for modified agouti C57BL/6N (JM8A3.N1) mES cells. When comparing blastocyst yield, super-ovulated B6NTac mice produced more injectable blastocysts per female than B6 albino mice (8.2 vs. 5.4). There was no significant difference in birth rate when injected embryos were transferred to the same pseudopregnant recipient strain. However, the live birth rate was significantly higher for B6NTac blastocysts than B6 albino blastocysts (62.7% vs. 50.2%). In addition, the proportion of pups exhibiting high-level and complete chimerism, as identified by coat color, was also significantly higher in the B6NTac strain. There was no obvious difference in the efficiency of germline transmission (GLT) when compared between B6NTac and B6 albino host embryos (61.5% vs. 63.3% for mES clones; 64.5% vs. 67.9% for genes, respectively), thus suggesting that an equivalent GLT rate could be obtained with only a few blastocyst injections for B6NTac embryos. In conclusion, our data indicate that B6NTac blastocysts are a better choice for the microinjection of JM8A3.N1 mES cells than B6 albino blastocysts.

Induction of micronuclei, nuclear anomalies, and dimensional changes in erythrocytes of the rare minnow (Gobiocypris rarus) by lanthanum - Yichen Qiu; Dong Hua; Jun Liu; Jianwei Wang; Bing Hu; Denghang Yu (Environmental Science and Pollution Research, 2020)

Comparative WGBS identifies genes that influence non-ripe phenotype in tomato epimutant Colourless non-ripening - Weiwei Chen; Zhiming Yu; Junhua Kong; Hui Wang; Yichen Li; Mei Zhao; Xiaohong Wang; Qianqian Zheng; Nongnong Shi; Pengcheng Zhang; Silin Zhong; Paul Hunter; et al. (Science China Life Sciences, 2018)

Effects of reduced pH and elevated pCO 2 on sperm motility and fertilisation success in blood clam, Tegillarca granosa - Wei Shi; Xinguo Zhao; Yu Han; Cheng Guo; Saixi Liu; Wenhao Su; Yichen Wang; Shanjie Zha; Xueliang Chai; Wandong Fu; Huicheng Yang; Guangxu Liu (New Zealand Journal of Marine and Freshwater Research, 2017)
Although it has been shown that ocean acidification generally has a negative impact on fertilisation success of broadcast spawning marine organisms, whether induced fertilisation success reduction is a consequence of elevated p CO 2 or decreased pH remains unclear. Therefore, the impacts of HCl‐ and CO 2 ‐induced acidified seawater on sperm motility and gametes fertilisation capability of a broadcast spawning bivalve species, Tegillarca granosa were investigated in the present study. The results showed that the fertilisation capability of both gametes was significantly reduced in either HCl‐ or CO 2 ‐acidified seawater. In addition, significant impacts on sperm motility were observed in the group exposed to CO 2 ‐acidified seawater, suggesting that this parameter is sensitive to p CO 2 instead of solely pH value. The differences between the two seawater acidification manipulating methods may be due to the intrinsic difference in diffusion capability of CO 2 and protons.

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Two newly identified sites in the N-terminal regulatory domain of Aurora-A are essential for auto-inhibition - Meirong Bai; Jun Ni; Sunqin Shen; Jiaxue Wu; Qiang Huang; Yichen Le; Long Yu (Biotechnology Letters, 2014)

SNIP1: a new activator of HSE signaling pathway - Qiang Li; Jian An; Xianghua Liu; Mingjun Zhang; Yichen Ling; Chenji Wang; Jing Zhao; Long Yu (Molecular and Cellular Biochemistry, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Systematic analysis of gene expression level with tissue-specificity, function and protein subcellular localization in human transcriptome - Qiang Li; Xianghua Liu; Quanyuan He; Lei Hu; Yichen Ling; Yanhua Wu; Xianmei Yang; Long Yu (Molecular Biology Reports, 2011)

Characterization of a novel human HMBOX1 splicing variant lacking the homeodomain and with attenuated transcription repressor activity - Mingjun Zhang; Shuai Chen; Qiang Li; Yichen Ling; Jie Zhang; Long Yu (Molecular Biology Reports, 2010)

Characterization of a novel human CDK5 splicing variant that inhibits Wnt/β-catenin signaling - Qiang Li; Xianghua Liu; Mingjun Zhang; Guangming Ye; Qian Qiao; Yichen Ling; Yanhua Wu; Yuanyuan Zhang; Long Yu (Molecular Biology Reports, 2010)